1998
DOI: 10.1063/1.476105
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative adsorption of H2 on Cu(100): Fixed-site calculations for impact at hollow and top sites

Abstract: We present results of six-dimensional ͑6D͒ quantum wave-packet calculations for the dissociative adsorption of (ϭ0,jϭ4,m j ) H 2 on Cu͑100͒. The potential-energy surface is a fit to points calculated using density-functional theory ͑DFT͒, with the generalized gradient approximation ͑GGA͒, and a slab representation for the surface. New aspects of the methodology we use to adapt the wave function to the symmetry of the surface, which relate to calculations for initial rotational states with odd m j ͑the magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 79 publications
3
18
0
Order By: Relevance
“…The domination of vibrational de-excitation by collisions at top sites is consistent with results obtained using a 2D model [9][10][11][12] to examine the scattering of ground state H 2 from Cu͑100͒ which showed that reaction is more likely in collisions with bridge or hollow sites and vibrational excitation occurs primarily at the top site. Specifically, twodimensional calculations 9,10 with the molecular axis held fixed parallel to the surface predict vibrational excitation probabilities of up to 40% for impact at a top site.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…The domination of vibrational de-excitation by collisions at top sites is consistent with results obtained using a 2D model [9][10][11][12] to examine the scattering of ground state H 2 from Cu͑100͒ which showed that reaction is more likely in collisions with bridge or hollow sites and vibrational excitation occurs primarily at the top site. Specifically, twodimensional calculations 9,10 with the molecular axis held fixed parallel to the surface predict vibrational excitation probabilities of up to 40% for impact at a top site.…”
Section: Resultssupporting
confidence: 76%
“…The results of 3D and 4D calculations, in which the position of the molecular center-of-mass is fixed above the high-symmetry bridge, 11 hollow, and top sites 12 are shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Previous to these, theoretical studies of surface reactions were restricted to explaining experimental trends, because to obtain a quantitatively accurate picture of dissociative chemisorption of diatomic molecules on metal surfaces, it is necessary to consider all six molecular degrees of freedom. 2,[16][17][18] Nonetheless, reduced dimensionality ͑2D-4D͒ calculations 16,[19][20][21][22][23][24][25][26][27] have played, and will continue to play, a very important role in understanding the trends found experimentally.…”
Section: Introductionmentioning
confidence: 99%